Social Anxiety and Quality of Life in Vitiligo and Acne Patients with Facial Involvement: A Cross-Sectional Controlled Study - SALMAN, ANDAÇ; TOPÇUOĞLU, VOLKAN (ADIS INT LTD, 2016)
Vitiligo and acne vulgaris, commonly affecting the face, have significant psychological effects and impair the quality of life of the affected individuals. Because of their negative effect on physical appearance, these conditions may act as a potential barrier to social relationships and cause social anxiety. The objective of the study was to investigate the social anxiety, quality of life, anxiety, and depression levels of acne and vitiligo patients with facial involvement and compare these levels with healthy controls. Thirty-seven vitiligo and 37 acne patients, aged older than 18 years, with facial involvement and 74 age- and sex-matched healthy control subjects were included in the study. The patients and healthy controls were asked to complete the Liebowitz Social Anxiety Scale, the Hospital Anxiety and Depression Scale, and the Dermatology Life Quality Index. Disease severity was evaluated both objectively by the physician and subjectively by the patients using a visual analog scale. Social anxiety, depression, and anxiety levels of vitiligo and acne patients were significantly higher than healthy controls (p < 0.05). Quality of life was impaired in both patient groups (Dermatology Life Quality Index scores for vitiligo: 5.6 +/- A 5.1; acne: 6.4 +/- A 6.2). There was no correlation between psychiatric scale scores and disease severity. Quality of life was negatively correlated with social anxiety and depression levels in both patient groups in our study. Vitiligo and acne patients had higher levels of social anxiety, anxiety, and depression compared with healthy control subjects. Considering that increased psychosocial morbidity was regardless of age, sex, and disease severity and was correlated with quality of life impairment, evaluation of the psychosocial morbidity, in particular social anxiety, may be valuable in all vitiligo and acne patients.
Keywords: PSYCHIATRIC MORBIDITY; DERMATOLOGY PATIENTS; CLINICAL-VARIABLES; ATOPIC-DERMATITIS; TURKISH VERSION; DEPRESSION; PHOBIA; VULGARIS; INDEX; SEVERITY